Menakar Minat Masyarakat dalam Belajar Bahasa Isyarat: Antara Kesadaran Sosial dan Tren Komunikasi Inklusif - Livia Talisa Onggo (CV. ITTC INDONESIA, 2025)
Limited public understanding and access to sign language learning has contributed to ongoing communication barriers for the deaf community in Indonesia. This study aims to explore public interest in learning sign language, focusing on motivation, learning methods, challenges encountered, and its impact on interpersonal communication and social relationships. This study uses a descriptive qualitative approach through focus group discussions (FGD), involving three informants with different backgrounds: students, private employees, and workers in the creative industry. This technique allows researchers to obtain an in-depth picture of their experiences and perceptions of the sign language learning process. The findings reveal that primary motivations include curiosity, social media exposure, social empathy, and emotional connection. Learning methods vary from digital platforms to structured community-led classes. The main challenges are gesture complexity and limited access to formal learning tools. However, sign language education increases non-verbal sensitivity, enhances social connectedness, and cultivates a more inclusive society. Interpersonal communication theory and diffusion of innovation theory prove effective in explaining how sign language is adopted by the wider public. This underscores the importance of cross-sector collaboration to broaden access and support for sign language learning as part of inclusive communication efforts in Indonesia. Cross-sector collaboration is essential to expand access and support for sign language learning as part of promoting inclusive communication in Indonesia.